The annual training and competitive calendar in elite football: A road to the holy grail? - Fazackerley, L.; Minett, G.; McLaren, S.; Ward, P.; Marsh, D.; Burgess, D.; Duncan, C.; Pollard, B.; Griffith, S.; Gill, N.; Kelly, V. (International Journal of Strength and Conditioning, 2023)
Organisations governing football codes worldwide continually seek to optimise the balance between their match calendar and commercial revenue. For many competitions, the result is more matches, and consequently, increased workload and travel demands for players. However, as competitions expand, the greater volume and/or intensity of workload challenges coaches` best practices in balancing performance with recovery and injury risk. This current perspective article aims to overview the annual training and competition calendar of professional football codes and competitions internationally. There is a vast difference in the length and structure of each component of football macrocycles, which appears dependent on the physiological capabilities required to compete in each code successfully. However, there is little research to justify the season`s structure of any football code. The importance of athlete physical and mental health is highlighted, and discussed the limitations and restrictions governing bodies implement to protect players. In conclusion, future research to improve the structure of the annual training and match calendar should incorporate a framework of both physiological and psychological components to support elite football athletes better.